Predicting dog tracheal diameter and length: A tool for improved intubation - Khiao in, Maneenooch; Kananub, Suppada; Sritrakul, Tepyuda; Thamsatit, Pattarawadee; Theerawatanasirikul, Sirin; Srisowanna, Naparee (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aims to develop formulas for estimating tracheal diameter and length in dogs using easily measurable anatomical parameters. Materials and Methods: The samples consisted of 20 dogs of various breeds, comprising 10 males and 10 females, sourced from cadavers. The measured parameters included occipital tuberosity to tail base (OT), eye angle to ear tragus, nose to ear tragus, inner vertical diameters (IVD), and tracheal length (TL). The study conducted correlation and linear regression analyses, and subsequently, the formulated models underwent validation using 16 live dogs. The results were compared to radiographic measurements. Results: Linear regression recommended formulas based on OT, resulting in IVD (mm) = 0.203 × OT – 3.724 (r2 = 0.608, p < 0.001) and TL (cm) = 0.346 × OT–3.773 (r2 = 0.837, p < 0.001). The predicted tracheal diameter and length from formulas were slightly smaller than radiographic measurements (IVD = 2.76 ± 1.85 mm, p < 0.0001 and TL = 2.07 ± 1.81 cm, p < 0.0001). Conclusion: These formulas offer a practical way to estimate tracheal dimensions in live dogs, facilitating the selection of suitable endotracheal tube sizes and insertion depth. Further studies with larger sample sizes and consistent measurement methods can enhance the accuracy of these findings. Adv. Vet. Anim. Res., 11(2): 323-329, June 2024 http://doi.org/10.5455/javar.2024.k780